(untitled) (International Journal of Engineering and Computer Science, 2024)
In the world of computing and networking, it is critical to understand the theoretical framework that underlies data communication to ensure the best performance and compatibility between various systems. Both the Open Systems Interconnection (OSI) and Transmission Control Protocol/Internet Protocol (TCP/IP) models offer a comprehensive perspective on how the entire communication operation is separated into various layers, with each layer assigned particular roles and functions. This paper compares the OSI and TCP/IP models in terms of the functionalities and responsibilities of the various layers in each model, with an emphasis on how these layers work together to ensure effective and robust network communications. The paper covers encapsulating and decapsulating processes, managing sessions, and ensuring reliable data transmission. The TCP/IP model focuses on practical application with four main layers, while the OSI model has seven detailed layers that provide a theoretical and structured approach. The goal of both models is reliable and standardized communication, which in turn promotes interoperability in a variety of network environments.